Associations of Bioavailable Serum Testosterone With Cognitive Function in Older Men: Results From the National Health and Nutrition Examination Survey. Issue 1 (5th August 2022) - Giannos, Panagiotis; Prokopidis, Konstantinos; Church, David D; Kirk, Ben; Morgan, Paul T; Lochlainn, Mary Ni; Macpherson, Helen; Woods, David R; Ispoglou, Theocharis
Abstract: Background: Age-associated cognitive decline may be influenced by testosterone status. However, studies evaluating the impact of bioavailable testosterone, the active, free testosterone, on cognitive function are scarce. Our study determined the relationship between calculated bioavailable testosterone and cognitive performance in older men. Methods: We used data from the U.S. National Health and Nutrition Examination Survey (NHANES) between 2013 and 2014. This study consisted of 208 men aged ≥60 years. Bioavailable serum testosterone was calculated based on the total serum testosterone, sex hormone–binding globulin, and albumin levels, whereas cognitive performance was assessed through the Consortium to Establish a Registry for Alzheimer's Disease (CERAD) Word List Learning Test (WLLT), Word List Recall Test (WLRT), and Intrusion Word Count Test (WLLT-IC and WLRT-IC), the Animal Fluency Test (AFT), and the Digit Symbol Substitution Test (DSST). Multiple linear regression analyses were performed upon adjustment for age, ethnicity, socioeconomic status, education level, medical history, body mass index, energy, alcohol intake, physical activity levels, and sleep duration. Results: A significant positive association between bioavailable testosterone and DSST (β: 0.049, p = .002) score was detected, with no signs of a plateau effect. No significant associations with CERAD WLLT ( p = .132), WLRT ( p = .643), WLLT-IC ( p = .979), and WLRT-IC ( p = .387), and AFT ( p = .057) were observed. Conclusion: Calculated bioavailable testosterone presented a significant positive association with processing speed, sustained attention, and working memory in older men above 60 years of age. Further research is warranted to elucidate the impact of the inevitable age-related decline in testosterone on cognitive function in older men.